THE EFFECT OF VISCOSITY AND SALIVA BUFFER IN DIABETES MELITUS PATIENTS ON THE DENTAL CARIES: PENGARUH VISKOSITAS DAN BUFFER SALIVA TERHADAP TERJADINYA KARIES GIGI PADA PASIEN DIABETES MELITUS - Wilda Hafni Lubis Lubis; Kavisha Prakas (Dentika: Dental Journal, 2019)
Oral complications will occur in the form of dental caries when Diabetes Mellitus (DM)is not controlled. The purpose of this study was to determine the effect of viscosity and salivary buffer on the severity of dental caries in DM patients. This research is an analytic survey with cross sectional approach involving 61 subjects (42 women and 19 men) who are patients with type II DM in Dr. PirngadiHospital Endocrine Clinic Medan. This research was conducted by carrying out an oral examination to calculate the DMF-T index and visual measurement of the saliva viscosity and salivary buffer by using a buffer test strip. The results obtained from this study showed that there are 77.0% DM patients who experienced dental caries and 23.0% DM patients who did not experience dental caries. Based on saliva viscosity, subjects had poor saliva viscosity (80.3%). This study also showed that salivary buffer in DM patients was low (67.2%). Data were analyzed by chi-square test showed significant results (p <0.05) with a significant value of p = 0,000. The significance value of the effect of salivary buffer on DM patients with the occurrence of dental caries is p = 0.02. Based on these results, it can be concluded that there is a significant effect between viscosity and salivary buffer with the occurrence of dental caries.